Rekonstruksi Keseimbangan Kontraktual dalam Perjanjian Kredit Perbankan: Kritik terhadap Dominasi Klausula Baku Pasca Pojk Perlindungan Konsumen 2023 - Jauw Shinta Dewi; Yuyut Prayuti (Jurnal Hukum Lex Generalis, 2026)
The revision of national banking regulations through the issuance of the POJK Consumer Protection (2023) is an important milestone in efforts to restore contractual balance between banks and consumers. However, empirical practice shows that standard clauses still dominate the structure of credit agreements, resulting in a significant imbalance in bargaining power. This study examines the extent to which the dominance of standard clauses limits contractual fairness in banking credit relationships and formulates a model for reconstructing balance in line with the principles of civil law, prudence and consumer protection. The results of the discussion emphasize the need for reconstruction through transparency, risk proportionality and effective judicial oversight. It is concluded that the harmonization of civil law and prudential standards is absolutely necessary to achieve balance and consumer protection in national banking practices in a fair and sustainable manner in the future.